Schroder [large type] : a novel - Gaige, Amity, 1972- (Thorndike Press, 2013)
Attending a New England summer camp, young Eric Schroder-a first-generation East German immigrant-adopts the last name Kennedy to more easily fit in, a fateful white lie that will set him on an improbable and ultimately tragic course. SCHRODER relates the story of Eric's urgent escape years later to Lake Champlain, Vermont, with his six-year-old daughter, Meadow, in an attempt to outrun the authorities amid a heated custody battle with his wife, who will soon discover that her husband is not who he says he is. From a correctional facility, Eric surveys the course of his life to understand-and maybe even explain-his behavior: the painful separation from his mother in childhood; a harrowing escape to America with his taciturn father; a romance that withered under a shadow of lies; and his proudest moments and greatest regrets as a flawed but loving father.